Proceedings of the Canadian Thyroid Cancer Active Surveillance Study Group 2019 national investigator meeting - David P. Goldstein; Sangeet Ghai; Martin Corsten; Eric Bissada; Nathalie Audet; Han Zhang; Anthony Nichols; Deric Morrison; Stephanie Johnson-Obeski; Donald W. Anderson; Eitan Prisman; Nancy N. Baxter; et al. (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Active surveillance (AS) in the management of small, low risk papillary thyroid cancer (PTC) as an alternative option to thyroidectomy, is an area of active research. A national Canadian study is proposed to evaluate the long-term outcomes of patients with small, low risk PTC who choose AS or surgery. This letter describes the proceedings of a national investigator meeting to plan the study. Graphical abstract